First isolation of Ascotricha chartarum from bronchoalveolar lavage of two patients with pulmonary infections. (March 2019) - Khan, Z.; Ahmad, S.; Jeragh, A.; Alfouzan, W.; Al Foudri, H.; Hassan, N.; Asadzadeh, M.; Joseph, L.; Varghese, S.
Abstract: Ascotricha chartarum is a rare human pathogen. We describe the isolation and characterization of A. chartarum from bronchoalveolar lavage samples of two patients with underlying pulmonary infections. The identity of both isolates was established by typical phenotypic characteristics and by sequencing of the internal transcribed spacer region and D1/D2 domains of recombinant DNA and β-tubulin gene fragment. The demonstration of branched, septate hyphae in direct microscopic examination of both the specimens and isolation of the fungus in pure cultures suggest its aetiologic role in the disease process. Because of phenotypic similarities of A. chartarum with Chaetomium spp. and other Chaetomium -like fungi, the application of molecular methods is needed for its accurate identification. Although in the absence of histopathologic evidence the aetiologic role of A. chartarum could not be established unequivocally, nonetheless, in view of the rarity of its isolation from clinical specimens and demonstration of hyphal elements in bronchoalveolar lavage sample, this report assumes considerable significance. It serves to create awareness about environmental fungi that previously have missed attention but may play a role in respiratory infections.